Innovation policy in Ireland and Northern Ireland, 1991 to 2001 – the changing face of enterprise-level financial incentives for R&D - Nola Hewitt-Dundas; Bernadette Andreosso-O'Callaghan; Helena Lenihan (European Regional Science Association (ERSA), 2005)
Systemic thinking on innovation policy highlights the breadth of policies which can influence innovation e.g. skills, inward investment, enterprise, regulation and competition policy. This suggests that innovation policy must be examined holistically, both in terms of the framework conditions to promote innovation as well as in terms of more targeted or specific policy to promote innovation at the enterprise level e.g. financial incentives to enterprises. It has been suggested that national innovation policy tends to reinforce the strengths of a country's industrial system, particularly in relation to large firms and the promotion of R&D in core technologies and focuses less on innovation transfer which is often left to regional technological policy initiatives. In lagging regional economies, which are often dominated by SME's, this presents specific challenges for innovation policy. This paper presents a comparative analysis of innovation policy at both the national and regional levels in Ireland and Northern Ireland respectively, over the 1990s. In both Ireland and Northern Ireland the period from 1991-99 was marked by expansion as measured by steady output growth for manufacturing as a whole (albeit at substantially lower levels in Northern Ireland than in Ireland). In Ireland this largely reflected rapid economic growth of output in the high-tech sectors, itself a consequence of inward investment and re-investment. Despite growth in gross expenditure on R&D over the 1990s closely related to output growth, Ireland's investment in R&D (at 0.95% of GNP) lags behind Slovenia, Norway, the UK, Austria, Netherlands, Belgium, Denmark, France, Germany, Finland, Sweden, the US and Japan. This paper assesses the role of national innovation policy in Ireland and regional innovation policy in Northern Ireland. A number of issues are addressed, such as; to what extent did innovation policy in Ireland and Northern Ireland merely sustain prevailing economic strengths or was it instrumental in overcoming specific deficiencies in R&D investment and moulding current economic strengths? What effect does the underlying industrial structure have in shaping innovation policy in terms of industrial sectors, ownership and the size distribution of firms? What differences are evident between national innovation policy initiatives and regional innovation initiatives, particularly in a lagging region? Innovation policy is examined in terms of targeted assistance i.e. direct government financial support for business sector investment in R&D. This is based on a database of all grant offers (Northern Ireland) and payments (Ireland) made by the industrial development agencies in Ireland and Northern Ireland over the 1991 to 2001 period which was developed for this paper. The paper emphasises issues concerning the concentration of R&D investment, change in the balance between pre-competitive and near market R&D and the move towards financial incentives for innovation transfer of R&D.
Keywords: 330